MENUJU MAâRIFATULLAH Menyelami Samudera Sufisme Imam al-Ghazali - AS, Asmaran (Faculty of Ushuluddin and Humanities, 2016)
Maârifatullah (knowing Allah) is a foundation of Islamic teaching because it is a vital part of MuslimâsÂ faithful. Other Teachings of Islam stand on it, because without the strong foundation such as knowing Allah sturdily, perhaps, the someone will notÂ do his obligation, or at least what he is doing doesnât have any useful for himslefÂ as a pleasant of life nor for another people as a good behave in society. There is a question to be answerd: What is the nature of maârifatullah? In particular, This question deepens in sufism of Imam al-Ghazali toward Maârifatullah. Mentioned here toward Maârifatullah, because a Muslim is only able to know Allah as in accordance with his limited ability to Allah, who is unlimited. According to al-Ghazali, Maârifatullah meansÂ convincing âknowledgeâ. It happens if the object is uncovered clearly without any hesitations. It means revealed of the secrets of divinity and all secrets of His creations. This circumstance cannot be reached by senses of experience and or logical reasoning, but it is purely a gift or divine inspiration from God through nÃ»r which is given to heart. Thus, it opens up all secrets are there behind this reality, which is not able to reach by someoneâs sense and mind. The circumstance is called as mukÃ¢syafah. At the time, someone i sable to know Allah through the manifestation of His creation. Imam al-Ghazali had told that maârifatullah is âlooking at Allahâs faceâ. Of course, it means looking at the visible manifestation of Allah traits in this universe.